1999
DOI: 10.1161/01.hyp.34.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(1–7) Is a Modulator of the Human Renin-Angiotensin System

Abstract: Abstract-The renin-angiotensin system is important for cardiovascular homeostasis. Currently, therapies for different cardiovascular diseases are based on inhibition of angiotensin-converting enzyme (ACE) or angiotensin II receptor blockade. Inhibition of ACE blocks metabolism of angiotensin-(1-7) to angiotensin-(1-5) and can lead to elevation of angiotensin-(1-7) levels in plasma and tissue. In animal models, angiotensin-(1-7) itself causes or enhances vasodilation and inhibits vascular contractions to angiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 39 publications
9
119
1
3
Order By: Relevance
“…16,18,[25][26][27] Thereby, the increase of ACE2 is a potential reason for the antihypertensive effect of atRA in SHR by attenuating the vasoconstrictive effect of Ang II, promoting the formation of Ang 1-7 and subsequently facilitating the release of NO.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,[25][26][27] Thereby, the increase of ACE2 is a potential reason for the antihypertensive effect of atRA in SHR by attenuating the vasoconstrictive effect of Ang II, promoting the formation of Ang 1-7 and subsequently facilitating the release of NO.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, it simultaneously reduced the maximum effect of Ang I, and identical observations were made toward Ang II. 19,20 This suggests that the Ang-(1-7) concentrations that selectively block the C-domain are also capable of blocking AT 1 receptors, thereby not allowing us to demonstrate the functional consequence of selective C-domain inhibition by Ang-(1-7) toward Ang I.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of AT 1 receptor is in line with studies showing that Ang-(1-7) may either modulate the allosteric binding of Ang II to the AT 1 receptor or compete with Ang II for this binding site. 38,39 For example, in rabbit 39 and human arteries, 40 it has been demonstrated that Ang-(1-7) behaves as a specific noncompetitive antagonist of AT 1 . The involvement of a putative Ang-(1-7) receptor in many actions of this peptide, including the liberation of NO from bovine aortic endothelial cells, 23 was also demonstrated previously.…”
Section: Discussionmentioning
confidence: 99%